2021
DOI: 10.3390/su13116062
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Consumer Perspectives of Bio-Based Products—A Comparative Case Study from Ireland and The Netherlands

Abstract: The bioeconomy can support Europe’s transition to a low-carbon economy and help to meet key international, European and member state sustainability targets through the provision of bio-based products and energy derived from sustainably sourced biomass. A successful implementation of a bio-based economy in Europe will, however, require a profound transformation of our production and consumption patterns. Consumer behavior will play a major role in supporting the successful transition to a bio-based economy. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 16 publications
6
20
0
Order By: Relevance
“…One study on green purchasing behavior found that worries regarding the deterioration of the natural atmosphere (e.g., through climate alteration and waste production) are progressively transforming consumer buying behavior to green goods as alternatives to more orthodox goods (Zaremohzzabieh et al, 2020). A supporting study conducted among 18-75-year-old consumers in Ireland and the Netherlands found that consumers in both countries had comparatively optimistic viewpoints about bio-based or packed products (Gaffey et al, 2021). In this study, Irish consumers showed a significantly added optimistic outlook and preference for purchasing bio based or packaged products when compared to packaging made from other less environmentally friendly packaging or fossil-based products.…”
Section: Bio Products and Consumer Purchase Behaviormentioning
confidence: 99%
“…One study on green purchasing behavior found that worries regarding the deterioration of the natural atmosphere (e.g., through climate alteration and waste production) are progressively transforming consumer buying behavior to green goods as alternatives to more orthodox goods (Zaremohzzabieh et al, 2020). A supporting study conducted among 18-75-year-old consumers in Ireland and the Netherlands found that consumers in both countries had comparatively optimistic viewpoints about bio-based or packed products (Gaffey et al, 2021). In this study, Irish consumers showed a significantly added optimistic outlook and preference for purchasing bio based or packaged products when compared to packaging made from other less environmentally friendly packaging or fossil-based products.…”
Section: Bio Products and Consumer Purchase Behaviormentioning
confidence: 99%
“…The successful transition away from fossil-based plastic will require a profound transformation of production and consumption patterns and involve actors across different sectors (Gaffey et al, 2021). The environmental benefit of sustainable alternatives is not only dependent on the characteristics of the products, but also on consumer willingness to purchase these alternatives (Steenis et al, 2018).…”
Section: Consumer Demand: Attitudes and Willingness To Paymentioning
confidence: 99%
“…Human dependence on fossil fuels is the main driver of climate change (IPCC, 2014) and changing consumer behaviour will play a central role in the transition towards a sustainable energy system (Ketelsen et al, 2020) and materials (Gaffey et al, 2021). Earlier work suggests that consumers are generally positive towards and willing to pay more for biobased products.…”
Section: Introductionmentioning
confidence: 99%
“…The transition towards bioeconomy depends not only on the efforts of professionals and policymakers but also on the acceptance and involvement of society [24]-in particular, consumers. In a study among Dutch and Irish consumers [25], price was indicated as a key factor influencing the purchase of bio-based products (around half of consumers were unwilling to pay more for bio-based products). Consumers indicated that environmental sustainability is a significant factor when choosing between products, but biodegradability and compostability are more important aspects for them than bio-based origin, highlighting the need to improve consumer understanding of bio-based products [25].…”
Section: Circular Bioeconomymentioning
confidence: 99%
“…In a study among Dutch and Irish consumers [25], price was indicated as a key factor influencing the purchase of bio-based products (around half of consumers were unwilling to pay more for bio-based products). Consumers indicated that environmental sustainability is a significant factor when choosing between products, but biodegradability and compostability are more important aspects for them than bio-based origin, highlighting the need to improve consumer understanding of bio-based products [25]. Transparent legal status and legislation are also critical factors for the development of bioeconomy [24].…”
Section: Circular Bioeconomymentioning
confidence: 99%